2017
DOI: 10.1016/j.aott.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The relation between elbow range of motion and patient satisfaction after open release of stiff elbow

Abstract: ObjectiveThe aim of this retrospective study was to find out whether a cut off value existed for elbow flexion and extension after open surgical release of elbow contracture that would correlate with subjective patient satisfaction.MethodsThe study enrolled 77 patients (53 males and 24 females with a mean age of 35.1 (18–77) years at the time of operation) with elbow contracture who attended regular follow-up appointments for more than 12 months. The mean follow up period was 44.2 months (12–186). The preopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…[1,7] A study by Morrey et al in 1981, showed that people could perform daily activity if the ROM of the elbow was at least 30 0 - 130 0 in flexion-extension, and 50 0 in pronation and supination. Loss of extension greater than 30 0 and flexion less than 120 0 is classified as elbow stiffness [3]. Hotchkiss classify elbow stiffness in three categories: minimal, moderate, and severe (Table 1) [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,7] A study by Morrey et al in 1981, showed that people could perform daily activity if the ROM of the elbow was at least 30 0 - 130 0 in flexion-extension, and 50 0 in pronation and supination. Loss of extension greater than 30 0 and flexion less than 120 0 is classified as elbow stiffness [3]. Hotchkiss classify elbow stiffness in three categories: minimal, moderate, and severe (Table 1) [8].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, elbow is prone to trauma, and it is susceptible of developing complications such as stiffness and degeneration [1]. Abnormalities of the bone, soft tissue, or combination of both, which may be intra-articular or extra-articular, can cause loss of elbow motion [2,3]. Morrey et al stated that elbow functional range of motion (ROM) for daily activity are 30 0 - 130° of flexion-extension and 50° of pronation-supination in either direction [1].…”
Section: Introductionmentioning
confidence: 99%
“…To diminish bias because of different rehabilitation, we let all patients undergo the same rehabilitation protocol (see appendix). The objective outcomes during follow-up were surgical data, adverse events during follow-up, range of motion, the Mayo Elbow Score (MES) 8 and humeral alignment measured using plain radiographs. Subjective patient reported outcomes were measured by Oxford Elbow Score (OES) 9 .…”
Section: Patient Selection and Follow-upmentioning
confidence: 99%
“…In general, the elbow is characterized by a small intracapsular volume, leading to effusion, scarring, hemarthrosis, and ultimately thickening of the capsule. Owing to these anatomical characteristics, stiff elbow is a common occurrence after trauma [ 26 ].…”
Section: Complicationsmentioning
confidence: 99%